Discovering the self in Islam: Self-striving, self-regard, and self-neglect - Teke, Mustafa; Ismail, Nik Ahmad Hisham (UAD (Universitas Ahmad Dahlan) Press, 2016)
This study explored some self domains and reviewed them through Islamic perspective, more particularly self-knowledge and faith. It provided an extensive literature on particular concepts of selfstriving,self-regard, and self-neglect. To briefly point out, the self has many origins, however deeply noted as such heart, spirit, and psyche in Islam. From these, this study looked at the two known self domains: self-striving, and self-regard. Apart from these concepts, researchers differently chose selfneglect. With this, the study indicated the self-neglect is an important concept as defensive behavior and these all self concepts might be useful as a central of human nature for future experimental development.